Exploring Community Perceptions of Traditional Becak and Modern Mobility in Indonesian Transportation: Balancing Cultural Heritage and Innovation - Sidabutar, Revin Andre (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2024)
This research investigates the diverse array of community perceptions surrounding transportation in Indonesia, particularly concerning the coexistence of traditional modes, notably the iconic becak, and the emergence of modern transportation services exemplified by platforms like Go-Jek. Through a comprehensive exploration of community sentiments, this study unravels a complex tapestry of viewpoints, revealing contrasting attitudes towards preserving cultural heritage and embracing technological advancements. The research illuminates the sentiments of different community segments, wherein one faction advocates ardently for the preservation of traditional transportation, emphasizing the cultural significance and historical legacy embedded within the becak. Conversely, another segment gravitates towards the convenience, efficiency, and technological allure of modern transportation options, illustrating the allure of innovation in a rapidly evolving urban landscape. The findings of this research underscore the need for a delicate balance a balance between preserving tradition and embracing innovation. They underscore the significance of navigating towards a transportation landscape that harmonizes traditional values with technological advancements. Ultimately, this study presents a roadmap for transportation development in Indonesia that respects cultural heritage, caters to diverse community needs, and paves the way for a transportation ecosystem where tradition and innovation coexist harmoniously.